THYMOQUINONE LOADED SOLID LIPID NANOPARTICLE: FORMULATION, CHARACTERIZATION AND IN-VITRO CELL VIABILITY ASSAY. - RAMACHANDRAN SUREKHA,; VEDAGIRI AISHWARYA,; THANGARAJAN SUMATHI, (International Journal of Pharma and Bio Sciences, 2015)
The aim of the present research is to formulate and characterize solid lipid nanoparticles (SLNs) encapsulated Thymoquinone (TQ) to improve the bioavailability of the hydrophobic drug. Solid lipid nanoparticles loaded Thymoquinone (TQ-SLNs) were prepared using hot homogenization followed by micro emulsion method. TQ-SLNs were characterized for particle size, zeta potential, entrapment efficiency, transmission electron microscopy, X- ray diffraction and in-vitro cytotoxicity. Optimized TQ-SLNs with appropriate characteristics (Particle size = 172.10 ± 7.41 nm; Zeta potential = -45.40 ± 2.68 mV; Entrapment efficiency = 84.49 ± 3.36%) were fabricated. The in-vitro drug release data revealed a maximum of 86.15 ± 2.76% for TQ-SLNs in 72 hrs. TEM images showed a spherical surface of TQ-SLNs and uniform particle size distribution. The state of formulation was characterized by XRD and it exhibited the reduced crystallinity of the entrapped drug. In addition, TQ-SLNs showed a concentration-dependent increase in cytotoxic activity with IC50 value of 35.5 ± 10.5 µg/ml. The results of the present study demonstrate that TQ-SLNs are promising nanoformulations with significant characteristic nature and can be a potential delivery system for the treatment of various diseases.